Pengaruh Layanan Penguasaan Konten Berbantuan Media Video Untuk Mengurangi Perilaku Phubbing Pada siswa SMPN 3 Kota Bengkulu - Pasca Gempita, Sandra; Dharmayana, I Wayan; Mishbahuddin, Arsyadhani (UNIVERSITAS BENGKULU, 2023)
This study aims to describe the effect of content mastery services assisted by video media toreduce phubbing behavior in SMPN 3 Bengkulu City. This study used an experimental method with one group pre-test post-test design. The population is 163 students. The research sample was students who had a high level ofphubbing behavior. Data collection techniques using a questionnaire with a Likert scale. The research data were analyzed using a paired sample t-test with the help of the SPSS version 2.1 application. The results showedthat there was a decrease in thlevel of phubbing behavior in studentsafter being given cintent mastery services assisted by vide media. There is an influence of content mastery services assisted by video media on students phubbing behavior. The phubbing behavior of students before being given treatment was relatively high. The phubbing behavior of students after being given treatment decreased.Keywords: Phubbing Behavior, Video Media, Content Mastery Service